Characterization of saltern based Streptomyces sp. and statistical media optimization for its improved antibacterial activity - Rajeswari, Pandiyan; Jose, Polpass Arul; Amiya, Richa; Jebakumar, Solomon Robinson David (Frontiers in Microbiology, 2015)
A moderately halotolerent Streptomyces strain, designated JAJ13 was characterized and a culture medium was statistically optimized to improve its antibacterial activity. Based on the phenotypic and molecular characteristics, strain JAJ13 was identified as a moderately halotolerant Streptomyces sp. JAJ13. Novelty of the stain JAJ13 in production of antibacterial compound was assessed by sequence analysis of KSα gene and LC-MS analysis of the active compound. Optimization of the culture medium for antibacterial compound production by the strain JAJ13 was performed with statistical methodology based on experimental designs. Initially, a starch based basal production medium was selected out of eight different production media screened for antimicrobial compound production by Streptomyces sp. JAJ13. Plackett-Burman design was employed to screen the influential media components affecting the antibacterial compound production. Subsequently, statistical optimization of selected medium components was performed by employing the Response Surface Methodology (RSM) with Box-Behnken design. The optimum initial level of CuSO4.5H2O, (NH4)2SO4 and K2HPO4 for the highest antibacterial activity was determined to be at 4.45 mg, 1.96 g and 1.15 g in 1 L of distilled H2O, respectively. PBD and RSM guided design of experiments resulted in a maximum antibacterial activity of 23.37 ± 2.08 mm, which is a 78.8 % increase in comparison with that obtained in the unoptimized medium. This study points the success of statistical model in developing an optimized production media for enhanced antibacterial compound production by Streptomyces sp. JAJ13.